Comparative performance analysis of 2D and 3D gamma metrics for patient specific QA in VMAT using Octavius 4D with 2D-Array 1500. (November 2021) - Pal, Bipasha; Pal, Angshuman; Bag, Santanu; Ali, Md. Abbas; Das, Suresh; Palit, Soura; Sarkar, Papai; Mallik, Suman; Goswami, Jyotirup; Das, Sayan; Manir, Kazi Sazzad; Sen, Arijit; et al.
Highlights: Comparative performance analysis of 2D & 3D Gamma done with advanced equipment. Conclusive evidence of benefits in shifting from 2D to higher dimension geometries. Correlations show mixed results on interdependence of pass % at separate geometries. Performance aspects of 2D & 3D gamma should be examined to decide the PSQA metrics. Abstract: Introduction: Gamma pass percentage (GPP) is the predominant metric used for Patient Specific Quality Assurance (PSQA) in radiation therapy. The dimensionality of the measurement geometry in PSQA has evolved from 2D planar to 3D planar, and presently to state-of-the-art 3D volumetric geometry. We aim to critically examine the performance of the three-dimensional gammas vis-à-vis the older gamma metrics of lower dimensionality to determine their mutual fungibility in PSQA, using clinically approved Volumetric Arc Therapy (VMAT) plans. Methods and materials: Gamma pass percentages derived from PSQA for VMAT plans using Octavius 4D phantom with 2D-Array 1500 and its proprietary software were recorded. 2D planar, 3D planar, and 3D volumetric gamma pass percentages were retrospectively extracted for multiple treatment plans at three sites, using three acceptance limits, and for two modes of normalization. The differences in mean pass percentages, and the pairwise correlation between geometries were calculated within limits of statistical significance. Results: A significant increase in mean pass rates was observed from 2D planar to 3D planar geometries. The difference was less pronounced from 3D planar to 3D volumetric. 2D planar v/s 3D planar showed a significant degree of correlation among themselves, which was not seen against most of the 3D volumetric pass rates. Conclusion: The mean gamma pass rates show conclusive evidence of the benefits of shifting from 2D planar to higher dimensions measurement geometries, but the benefits of using 3D volumetric compared to 3D planar is not always unequivocal. The correlations show mixed results regarding the interdependence of pass percentages at different geometries.